Fifty shades of SUMO: its role in immunity and at the fulcrum of the growth–defence balance. (13th February 2018) - Verma, Vivek; Croley, Fenella; Sadanandom, Ari
Summary: The sessile nature of plants requires them to cope with an ever‐changing environment. Effective adaptive responses require sophisticated cellular mechanisms at the post‐transcriptional and post‐translational levels. Post‐translational modification by small ubiquitin‐like modifier (SUMO) proteins is emerging as a key player in these adaptive responses. SUMO conjugation can rapidly change the overall fate of target proteins by altering their stability or interaction with partner proteins or DNA. SUMOylation entails an enzyme cascade that leads to the activation, conjugation and ligation of SUMO to lysine residues of target proteins. In addition to their SUMO processing activities, SUMO proteases also possess de‐conjugative activity capable of cleaving SUMO from target proteins, providing reversibility and buffering to the pathway. These proteases play critical roles in the maintenance of the SUMO machinery in equilibrium. We hypothesize that SUMO proteases provide the all‐important substrate specificity within the SUMO system. Furthermore, we provide an overview of the role of SUMO in plant innate immunity. SUMOylation also overlaps with multiple growth‐promoting and defence‐related hormone signalling pathways, and hence is pivotal for the maintenance of the growth–defence balance. This review aims to highlight the intricate molecular mechanisms utilized by SUMO to regulate plant defence and to stabilize the growth–defence equilibrium.